Advancing Equality How Constitutional Rights Can Make a Difference Worldwide - Heymann, Jody (University of California Press, 2020)
In a world where basic human rights are under attack and discrimination widespread, Advancing Equality reminds us of the critical role of constitutions in creating and protecting equal rights. Combining a comparative analysis of equal rights in the constitutions of all 193 countries with inspiring stories of activism and powerful court cases from around the globe, the book traces the trends in constitution drafting over the past half century, and examines how stronger protections against discrimination have transformed lives. Looking at equal rights across gender, race and ethnicity, religion, sexual orientation and gender identity, disability, social class, and migration status, the authors uncover which groups are increasingly guaranteed equal rights in constitutions, whether these rights on paper have been translated into practice, and which nations and protections from discrimination lag behind. As the book reveals, beyond countering discrimination, advancing equality requires fulfilling everyone's fundamental rights to health and education, essential social and economic rights. Serving as a comprehensive call to action for anyone who cares about their country's future, Advancing Equality challenges us to remember how far we all still must go for equal rights for all.